Study on the Wrinkling Mechanisms of Human Skin Based on the Digital Image Correlation and Facial Action Coding System - Huixin Wei; Mingjian Chen; Shibin Wang; Zhiyong Wang; Baopeng Liao; Zehui Lin; Lisha He; Wei He (Applied Sciences)
Facial wrinkles are a key indicator of aging and hold significant importance in skincare, cosmetics, and cosmetology. Their formation is closely linked to mechanical deformation, yet the underlying processes remain complex. This study integrates the Facial Action Coding System (FACS) with three-dimensional digital image correlation (3D-DIC) to dynamically capture and quantitatively analyze skin deformation during facial expression. Principal strains and their orientation are introduced as important parameters to investigate the relationship between mechanical behavior and wrinkle formation. To further explore these interactions, a four-layer finite element (FE) model incorporating a muscle layer is developed, simulating muscle contraction and its influence on skin deformation. The findings provide a mechanobiological framework for understanding wrinkle formation and may inspire the development of strain-sensitive sensors for real-time detection of microstructural deformations.